Does COVID-19 Reduces Income and Wealth Inequality: Evidence from OIC Countries - Munandar, Aris (Sunan Kalijaga: Islamic Economics Journal, 2022)
This study investigated the effect of the COVID-19 pandemic on income and wealth inequality in the 56 Organization of Islamic Cooperation (OIC) member countries from 2010-2021. We employ a panel fixed effect model to estimate the relationship between a dummy COVID-19 outbreak and a comprehensive inequality proxy consisting of income and wealth inequality of the top 10%, bottom 50%, and top 1%, respectively. Findings suggest that while COVID-19 has contributed to a reduction in wealth inequality, it has not had a significant effect on income inequality. The restriction policies imposed during the pandemic have decreased the proportion of high-wealth individuals, but not the proportion of high-income earners. To further promote income equality, governments should focus on increasing foreign investment by improving the ease of doing business and enhancing political stability in the region.